Molly on the range : recipes and stories from an unlikely life on a farm - Yeh, Molly (Rodale, 2016)
"In 2013, food blogger and classical musician Molly Yeh left Brooklyn to live on a farm on the North Dakota-Minnesota border, where her fiancé was a fifth-generation Norwegian-American sugar beet farmer. Like her award-winning blog My Name is Yeh, Molly on the Range chronicles her life through photos, more than 120 new recipes, and hilarious stories from life in the city and on the farm. Molly's story begins in the suburbs of Chicago in the 90s, when things like Lunchables and Dunkaroos were the objects of her affection; continues into her New York years, when Sunday mornings meant hangovers and bagels; and ends in her beloved new home, where she's currently trying to master the art of the hotdish. Celebrating Molly's Jewish/Chinese background with recipes for Asian Scotch Eggs and Scallion Pancake Challah Bread and her new hometown Scandinavian recipes for Cardamom Vanilla Cake and Marzipan Mandel Bread, Molly on the Range will delight everyone, from longtime readers to those discovering her glorious writing and recipes for the first time"--